Classification, annotated list and keys for the black flies (Diptera: Simuliidae) of Peninsular Malaysia - Takaoka, Hiroyuki; Ya'cob, Zubaidah; Sofian-Azirun, Mohd (Magnolia Press, 2018)
The classification, annotated list and keys for the black fly species from Peninsular Malaysia are updated. The number of black fly species increased from 38 in 1995 to 62 (including a new species herein described) in 2018. The 62 species are classified in four subgenera of the genus Simulium: one species in Daviesellum, 35 species in Gomphostilbia, five species in Nevermannia and 21 species in Simulium. Species in the latter three subgenera are further placed in species-groups or subgroups. Keys are provided for females, males, pupae and mature larvae. Simulium (S.) perakense sp. nov. is described and placed in the S. striatum species-group. The males of S. (G.) decuplum, S. (G.) tahanense, S. (S.) malayense, the female of S. (G.) adleri, and the female and larva of S. (G.) varicorne are described for the first time. The female, male, pupa and larva of S. (G.) trangense, the male and pupa of S. (G.) varicorne and the pupa of S. (G.) adleri are redescribed. Simulium(G.) sp. A is identified as S. (G.) pegalanense. Brief notes for each species are given on morphological characteristics, aquatic habitats and geographical distributions.